A new ranking of IHRM journals: What type of quantitative research do they publish?. (May 2020) - Redondo, Raquel; Fabra, Maria Eugenia; Martín, Gloria
By analyzing content, this paper aims to map empirical quantitative research on International Human Resource Management. Our filters will be "when, where, what, and how." "When" indicates the time span we use to analyze the evolution of International Human Resource Management, "where" refers to the influential journals chosen for publication; "what" covers the different topics dealt with in IHRM, and "how" is linked to the various methodologies and statistical techniques applied. Using the "when, where, what, and how" of empirical quantitative, International Human Resource Management studies allows us to identify how different topics have been investigated and so may lead us to suggest methodological refinements to improve the analysis and knowledge of topics in International Human Resource Management. It will allow us to detect trends and research gaps and point to the most prominent journals for publication and dissemination of results.